From Trent to Vatican II historical and theological investigations - Bulman, Raymond F., 1933-; Parrella, Frederick J. (New York : Oxford University Press, 2006)
The second Vatican Council was convened by Pope John XXIII between 1962 and 1965. It marked a fundamental shift towards the modern Church. This book offers an examination of the nature and scope of these changes.
The historical context / Raymond F. Bulman -- From the Council of Trent to "Tridentinism" / Giuseppe Alberigo -- A marriage made in America: Trent and the baroque / Anthony M. Stevens-Arroyo -- The Council of Trent at the Second Vatican Council / Joseph A. Komonchak -- Robert Bellarmine and post-Tridentine eucharistic theology / Robert J. Daly -- The Latin of the Roman rite: before Trent and after Vatican II / Gerard S. Sloyan -- Priestly formation / Kenan B. Osborne -- Singing a new song unto the Lord: Catholic Church music / James J. Boyce -- Moral theology / James F. Keenan -- The Virgin Mary / Lawrence S. Cunningham -- The laity / Paul Lakeland -- Christian marriage / William P. Roberts -- Religious life for women: from enclosure to immersion / Doris Gottemoeller -- From confession to reconciliation and back: sacramental penance / W. David Myers -- Responding to religious difference: conciliar perspectives / Jeannine Hill Fletcher -- "Beset on every side": reimagining the ideology of the Roman catechism (1566) / Robert J. Brancatelli -- Trent and Vatican II: two styles of church / John W. O'Malley -- A clash of ecclesiologies / Frederick J. Parrella.
Includes index.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Catholic Church -- Doctrines -- History -- Modern period, 1500-; RELIGION -- Christian Theology -- Ecclesiology; Concilie Vaticanum II; Concilie van Trente; Conciliarisme; Rooms-Katholieke Kerk; Electronic books